Consumer Perceptions Analysis On Products Purchasing Interest in Citimall Matahari Department Store, Dumai City - Madhuri Nafasya Suswanda; Asmara Wildani Pasaribu; Hendra Hendra; Dany Perdana Sitompul (Yayasan Literasi Sains Indonesia, 2023)
Citimall Matahari Department Store is the largest contemporary retailer in the city of Dumai.So that every purchase of its products will certainly be based on their perception or assessment of the products sold and bought by Matahari Department Store. So this study aims to analyze the effect of perceived price, perceived quality and perceived lifestyle on purchase intention. The population in this study were visitors to Citimall Matahari Department Store in the city of Dumai who had purchased products. The number of samples is 100 respondents, using non-probability sampling method, accidental sampling. Respondent data was collected by distributing questionnaires. The data analysis technique was in the form of multiple linear regression analysis, with the help of IBM SPSS 26 software. The results showed (1). Price perception has a partial and simultaneous positive influence on the intention to buy Citimall Matahari Department Store products with a tcount of 3.681 (2). Perceived quality has a partial and simultaneous positive influence on the intention to buy Citimall Matahari Department Store products with a tcount of 3.665 (3). Perceptions of lifestyle have a positive influence partially and simultaneously on buying interest in Citimall Matahari Department Store products with a tcount of 4.233. The result of the adjusted R2 value is 0.490 while the remaining 0.510 is influenced by other variables not examined in this study Perceived quality has a partial and simultaneous positive influence on the intention to buy Citimall Matahari Department Store products with a tcount of 3.665 (3). Perceptions of lifestyle have a positive influence partially and simultaneously on buying interest in Citimall Matahari Department Store products with a tcount of 4.233. The result of the adjusted R2 value is 0.490 while the remaining 0.510 is influenced by other variables not examined in this study Perceived quality has a partial and simultaneous positive influence on the intention to buy Citimall Matahari Department Store products with a tcount of 3.665 (3). Perceptions of lifestyle have a positive influence partially and simultaneously on buying interest in Citimall Matahari Department Store products with a tcount of 4.233. The result of the adjusted R2 value is 0.490 while the remaining 0.510 is influenced by other variables not examined in this study.